Studies on the induction of cyanide-resistant respiration by H2O2 in aging potato tuber slices - LIANG Wu-sheng; LIANG Hou-guo; LI De-bao (浙江大学学报. 农业与生命科学版, 2002)
The influences of exogenous H2O2 on the cyanide resistant respiration in aging potato (Solanum tuberosum L.) tuber slices were investigated. Results showed that H2O2 (5.0 mmol/L) had a little influence on the total respiration (Vt) of the slices, but showed a significant inducing effect on the cyanide resistant respiration (Valt) and its contribution to total respiration (Valt/Vt) in the slices during 21 h of aging process. The significant inducing effects of H2O2 on the cyanide-resistant respiration were also found in mitochondria purified from the aging potato slices. Western blotting with monoclonal antibody against alternative oxidase showed that H2O2 treatment increased the expression of alternative oxidase in aging potato tuber slices, which implies that the induction of cyanide resistant respiration by H2O2 was related to alternative oxidase expression.